The Democratic People’s Republic of Korea’s Law on the Elimination of Reactionary Thought and Culture Under Kim Jong-Un’s Leadership - Dwijayani, Rista Herjani; Maksum, Ali (Faculty of Social and Political Sciences, Universitas Diponegoro, 2023)
This study aims to explain how Korean Wave, or Hallyu, influenced the enactment of theElimination of Reactionary Thoughts and Culture Laws in North Korea. To answer the ques-tions, this research used securitization theory and a qualitative descriptive method. The re-search combined several sources of literature, such as journals, books, the official website of the South Korean government, and several official reports from online media in East Asia. The results of the research show that the Law on the Elimination of Reactionary Thoughts and Culture, which was passed by the North Korean government, was caused by the negative assumptions made by the leader of the country about the spread of Hallyu or Korean Wave in his country. The various distributions of South Korean cultural content are viewed as a